Strategi Penggunaan Teknik dan Instrumen Evaluasi untuk Mengukur Hasil Belajar Kognitif Peserta Didik - wahyu, wahyu putra; Isropil siregar; Ardiansyah Syafruddin; Ridho Sutiawan (Sekolah Tinggi Ilmu Tarbiyah (STIT) Lingga, 2024)
This research aims to develop a strategy for using effective evaluation techniques and instruments to measure students' cognitive learning outcomes through a library research approach. The main problem identified was the mismatch between theoretically designed evaluation instruments and their application in diverse educational environments. This study analyzes various evaluation models and methods, and evaluates the effectiveness of their use in cognitive measurement. The research results show that the application of evidence-based evaluation techniques and innovative approaches can increase accuracy in assessing students' cognitive abilities.